Knowlege-Economy Dimensions in Promoting Economic Development - Case Study Of Arab Countries - - Sofiane ABAHRI; Mohamed MAGHNEM (المجلة الدولية للأداء الاقتصادي, 2023)
The current trends of education at the global level in general and the Arab world, in particular, are heading for the development of education towards the knowledge economy, where it has become an inevitability for education systems, which provides opportunities and challenges in the exploitation of technological capabilities, jobs, and new businesses, and this requires a workforce characterized by special qualities such as creativity, and speed of adaptation to external changes, and based on the above, the problem of the study is determined in the concept of the knowledge economy and its dimensions in promoting economic development in Arab.